Interventions or strategies to prevent and/or reduce alcohol consumption within the university population: A realistic review - Huertas, Mayra Solanye Galindo; López, Milena Alexandra Galvis; López, Luz Stella Algarra (Journal of Posthumanism, 2024)
Introduction: Alcohol consumption is a public health issue, as it is considered a multifactorial social problem with individual and collective effects. Motivated by multiple expectations, for young people, the consumption of alcohol also represents a way to approach others and have a sense of belonging. This realistic review aims to understand the impact interventions have on the prevention and/or reduction of the consumption of alcoholic beverages in a university population. Methodology: A bibliographical search was conducted in databases and other sources. After the screening and selection process, 13 documents were included. A theory of change was then put forward. Results and discussion: The theory was defined by a previous category titled “Youths, subjectivities of the subjects of law, from motivation, introspection, and self-awareness”. Two views on the matter are: 1) the existence of the individual and the potentiality in social participation and leisure; the youth is seen as a subject who makes and builds history; 2) the existence of the collective and the potentiality in social participation and leisure, from institutionalization, the sociohistorical moment, and the collective youth culture. Conclusions: Strategies for the reduction in the consumption of alcohol among young people should come from a place of respect, dialogue, and the recognition of autonomy that can allow them to see themselves as socio-historical subjects and agents of change from their own senses and meanings concerning their experience of leisure.